Case report: First report on human infection by tick-borne Babesia bigemina in the Amazon region of Ecuador - Manuel Calvopiña; María Montesdeoca-Andrade; Carlos Bastidas-Caldes; Carlos Bastidas-Caldes; Sandra Enriquez; Richar Rodríguez-Hidalgo; Richar Rodríguez-Hidalgo; Dayana Aguilar-Rodríguez; Philip Cooper; Philip Cooper (Frontiers Media S.A., 2023)
Babesiosis is a protozoan disease acquired by the bite of different species of ticks. More than 100 Babesia spp. infect wild and domestic animals worldwide, but only a few have been documented to infect humans. Generally, babesiosis is asymptomatic in immunocompetent persons; however, in immunocompromised can be life-threatening. A 13-year-old boy from the Amazon region presented with a 3-month evolution of fever, chills, general malaise, and arthralgia accompanied by anemia and jaundice. In the last 4 years was diagnosed with chronic kidney failure. By nested-PCR using 18S RNA ribosomal gene as target and DNA sequencing, the phylogenetic analysis showed Babesia bigemina as the causative agent in the blood. Treatment with oral quinine plus clindamycin for six continuous weeks was effective with no relapse occurring during 12 months of follow-up. This is the second human case in Ecuador but the first caused by the zoonotic B. bigemina which confirms the existence of active transmission that should alert public health decision-making authorities on the emergence of this zoonosis and the need for research to determine strategies to reduce tick exposure.